TLR9 Signaling Suppresses the Canonical Plasma Cell Differentiation Program in Follicular B Cells - Baptista, Bárbara José Antunes; Granato, Alessandra; Canto, Fábio B.; Montalvão, Fabricio; Tostes, Lucas; de Matos Guedes, Herbert L.; Coutinho, Antonio; Bellio, Maria; Vale, Andre M.; Nobrega, Alberto (Frontiers in Immunology, 2018)
The relative potency and quality of mouse B cell response to Toll-like receptors (TLRs) signaling varies significantly depending on the B cell subset and on the TLR member being engaged. Although it has been shown that marginal zone cells respond faster than follicular (FO) splenic B cells to TLR4 stimulus, FO B cells retain full capacity to proliferate and generate plasmablasts and plasma cells (PBs/PCs) with 2–3 days delayed kinetics. It is not clear whether this scenario could be extended to other members of the TLR family. Here, using quantitative cell culture conditions optimized for B cell growth and differentiation, we show that TLR9 signaling by CpG, while promoting vigorous proliferation, completely fails to induce differentiation of FO B cells into PBs/PCs. Little or absent Ig secretion following TLR9 stimulus was accompanied by lack of expression of cell surface markers and canonical transcription factors involved in PB/PC differentiation. Moreover, not only TLR9 did not induce plasmocyte differentiation, but it also strongly inhibited the massive PB/PC differentiation of FO B cells triggered by LPS/TLR4. Our study reveals unexpected opposite roles for TLR4 and TLR9 in the control of plasma cell differentiation program and disagrees with previous conclusions obtained in high-density cultures conditions on the generation of plasmocytes by TRL9 signaling. The potential implications of these findings on the role of TLR9 in controlling self-tolerance, clonal sizes and regulation of humoral responses are discussed.